SIFAT-SIFAT GEOTEKNIK BAHAN TIMBUNAN INTI KEDAP AIR BENDUNGAN BATUTEGI - Didiek Djarwadi (Forum Teknik, 2003)
Soil  was  already widely used  as watertight  materials  in  the  embankment  dam engineering, where as,  the  selection  and  treatment  (compaction)  will  in/Iuenced  the  geotechnical  properties.As  a water tight  material the  soil  used should  be  impermeable for controlling  seepage  and  hwe efficient  shear  strength for controlling  stability.The  aim  of  this  research  was to  analyze  the  soil laboratory  test  results  of core  embanlcrnentmaterials obtained  during the  soil investigation  and the  construction  stages  of  the  Batutegi dam,a 125  meter in  height  of earth-rockfill  dam in  Lampung, Indonesia.  The  research  analyzed  thegeotechnical  parameters  and  the  intercelations  of the  geotechnical  parameters  in  order  to indicate  the  geotechnical  properties  of the  core  embankment  materials.  The  evaluation  of the geotechnical  parameters from the soil laboratory  tests  indicated  that  in  term  of density,  permes-bility,  swelling  characteristic, compressibility  as  well as the  strength,  the  core  moterials  used at Batutegi  dam  meets  the  requirement  as watertight  materials  in the  embankment  dam engineering.Keywords:  geotechnical  properties,  embankment  dam,  water tight  materials.